Evaluation of the Expression of Matrix Metalloproteinase-1 of Laryngeal Squamous Cell Carcinoma by Ultrasound Molecular Imaging - Zhou, Yi; Song, Zhuqing; Hu, Qiao; Ji, Xiaojuan; Zheng, Hongyu; Wang, Xiaoyan; Li, Zhenzhou (Frontiers in Pharmacology, 2019)
ABSTRACT Purpose To evaluate the expression levels of Matrix metalloproteinases-1 (MMP-1) on Laryngeal Squamous Cell Carcinoma (LSCC) and improve the early diagnosis rate via ultrasound molecular imaging (USMI). Methods The microsized MMP-1-targeted microbubbles (MBMMP-1) and the control MBs (MBIgG) based on perfluorocarbon-filled lipid-shelled were constructed and characterized. The in vitro, binding experiment was performed with human epidermoid laryngeal cancer cells (HEp-2) and tested the binding efficiency of MBMMP-1 and MBIgG was tested. In the in vivo study, the LSCC model was established in 10 mice. The MBMMP-1 and MBIgG were randomly injected into tumor-bearing mice via the tail vein at Day 7, Day 12 and Day 17 to dynamically evaluate the differential Target Enhancement (dTE) signals via USMI. Subsequent immunofluorescence analysis was used for confirmation of MMP-1 expression. Result MBMMP-1 could effectively adhere to HEp-2 in the in vitro binding experiment higher than that of MBIgG with 298.42 ± 16.57 bubbles/per field versus 12.38 ± 3.26 bubbles/per field, (P< 0.01). The in vivo USMI results, demonstrated that dTE signal intensity from MBMMP-1was significantly higher than the MBIgG at Day 7, Day 12 and Day 17 (Day 7, 41.21 ± 15.00 a.u versus 2.25 ± 0.6 a.u, P< 0.05, Day 12, 124.64 ± 5.19 a.u versus 11.13±1.13 a.u, P< 0. 05, Day 17, 332.01 ± 64.88 a.u versus 42.99 ± 11.9 a.u, P< 0.01). Moreover, immunofluorescence analysis further confirmed the expression levels of MMP-1 in LSCC with a gradual increase with the tumor growth. Conclusion MBMMP-1 could be a potential probe which can be used to early diagnosis of LSCC by USMI.